Development of real-time reverse transcription polymerase chain reaction assays to quantify insulin-like growth factor-1 receptor and insulin receptor expression in equine tissue - Schulman, Martin L. (University of Pretoria, 2013)
Dissertation (MMedVet)--University of Pretoria, 2011.